Recovery of copper and nickel hydroxide from galvanic sludge : pilot scale experiments - Vilarinho, Cândida (2012)
The present work has been developed under the scope of the project VALMETAIS and proposes a hydrometallurgical process for copper and nickel hydroxide recovery from galvanic sludges produced by Ni/Cr plating plants. In this project. the procedure has been developed at a laboratory scale and validated at a small sized pilot plant. The developed procedure includes a first stage of a counter-current sulphuric leaching process of sludges in in three stages. Extraction rates of 99% for Cu and Ni were achieved under the leaching conditions above mentioned. The solid residue separated from the leaching solution is mostly constituted by gypsum (CaSO4) presenting a metal content below 1%. In order to recover selectively the copper from the leaching solution, a cementation process was carried out using iron scrap and performed at a pH of 2, which was achieved through adding new sludge to the filtered previous solution. The recovery rate of copper was 99%, producing cement with a high purity grade which enables its application as a commercial product. Nickel hydroxide precipitation was performed by adding sodium hydroxide to the cemented solution purified. Results showed a successfully nickel hydroxide extraction rate of 99% and a purity grade of more than 98%. These evidences demonstrate the high potential of the developed methodology in treating and obtaining economic benefits from galvanic sludge. The end products, namely the cooper and the nickel hydroxide, as well as the gypsum based sludge resulting from the leaching process, can be applied as commercial products or as component materials generating benefits.